Individual variation in rates of senescence: natal origin effects and disposable soma in a wild bird population. - Bouwhuis, S; Charmantier, A; Verhulst, S; Sheldon, B (2010)
1. Longitudinal studies of various vertebrate populations have recently demonstrated senescent declines in reproductive performance and/or survival probability with age to be almost ubiquitous in nature. Little is known, however, about the extent to which rates of senescence vary between individuals, and about causes or consequences of such variation. Quantifying these links in natural populations is important for understanding the constraints and adaptive processes underlying the evolution of senescence. 2. Here, we analyse breeding data from 1029 female great tits Parus major to quantify the effect of natal conditions and early life reproduction on rates of reproductive senescence, reproductive life span and lifetime reproductive success. 3. Although for locally born females we find no evidence that natal conditions influence rates of reproductive senescence, we show that immigrant females suffer from faster rates of senescence than locally born females, and that this difference contributes to immigrants having a lower lifetime reproductive success. 4. Additionally, and independently, we find rates of reproductive senescence to increase with rates of early life reproduction, as predicted by the disposable soma hypothesis. Despite accelerated senescence late in life, high early life reproduction is, however, positively associated with lifetime reproductive success across individuals. 5. Female immigrant status and early life reproduction do not relate to reproductive life span. 6. We thus show that both immigration into our population, and high levels of early life reproduction, are associated with reduced late life reproductive performance in female great tits, but that fitness can be increased by high levels of early life reproduction at the expense of accelerated reproductive senescence. These results suggest disposable soma to be a likely mechanism underlying senescence in these birds, and encourage further study of the genetic basis (i.e. antagonistic pleiotropy) of such an early vs. late life trade-off.